Genetic elements of a long-standing family business: An analysis of five century-old family businesses based on grounded theory - Qi Wang (Heliyon)
Succession is a major threat to the sustainable growth of family businesses. This study proposes that the growth of a family business is a co-evolutionary process involving multiple memes, and a family business undergoes succession through memes. To address this exploratory question, the author analyzes entrepreneurial behavior in five well-known century-old Western family enterprises based on grounded theory, and constructs a deoxyribonucleic acid model of the family business. The model not only reveals the most prominent memes in the complex meme system of a family business, but also illustrates the connectivity of different strengths among the organizational memes. The implications and recommendations derived from this study indicate that family businesses should develop specialization and succession capabilities through memes, and explore different means of innovation and adaptation to realize cross-generational growth.